Adenoviral transfer of a single donor-specific MHC class I gene to recipient bone marrow cells can induce specific immunological unresponsiveness in vivo - Fry, J; Morris, P; Wood, K (2002)
We investigated the delivery of a donor-specific MHC class I gene, H-2Kb, using a newly constructed replication-defective recombinant adenovirus (AdSV40Kb) to recipient tissue before transplantation as a means of inducing donor-specific immunological unresponsiveness. AdSV40Kb was able to transduce both a fibroblast cell line and freshly isolated bone marrow cells (BMCs) resulting in cell surface expression of H2-Kb protein. Intravenous infusion of AdSV40Kb-transduced syngeneic CBA/Ca (H-2k) BMCs into CBA recipient mice treated with an anti-CD4 monoclonal antibody 27 days before transplantation of a fully MHC-mismatched, C57BL/10 (H-2Kb+), cardiac allograft resulted in significant long-term graft survival when compared with mice receiving the same dose of syngeneic BMCs transduced with a control adenovirus, AdRSVβgal. Despite the induction of H-2Kb-specific hyporesponsiveness following pretreatment with AdSV40Kb-transduced CBA BMCs, persistence of H-2Kb mRNA in central or peripheral tissues could not be demonstrated by RT-PCR. This result was in contrast to the observed persistence of Kb mRNA both in the periphery and thymus following the infusion of transgenic CBK (H-2k + Kb) BMCs. We conclude that ex vivo adenoviral gene transfer of a single donor MHC class I gene to recipient BMCs in combination with transient depletion of CD4+ cells is sufficient to induce long-term graft survival of a fully allogeneic cardiac graft. In addition, detectable microchimerism is not a prerequisite for graft survival.